Origin of interstitial water beneath the continental shelf offshore northwestern Australia: insights from hydrogen and oxygen isotope compositions - Kosuke Yoshii; Hideko Takayanagi; Toshihiro Miyajima; Lars Reuning; Kazuyuki Yamamoto; Yasufumi Iryu (Progress in Earth and Planetary Science)
Abstract We analyzed the hydrogen and oxygen isotope compositions of interstitial water collected from Miocene–Quaternary carbonate platforms beneath the continental shelf margin off northwestern Australia during the International Ocean Discovery Program Expedition 356. By integrating isotope data with onboard salinity and chemical concentration measurements, we investigated the behavior of interstitial water in this continental shelf system. The interstitial water was classified into three groups based on salinity. Group 1 (salinity = 34−40) consisted of upper low-salinity water infiltrating from the modern seafloor, transitioning downward into highly saline water. This high-salinity water likely formed in situ during glacial periods. Group 3, characterized by extremely high salinity (salinity = 101−153), likely originated from the Late Miocene seawater modified by evaporation in an arid coastal environment. Group 2 (salinity = 43−98) represented a mixture of Groups 1 and 3. This study offers valuable insights into the hydrology of modern and ancient carbonate platforms, with implications for similar systems worldwide.